Successful engineering of a highly potent single-chain variable-fragment (scFv) bispecific antibody to target disialoganglioside (GD2) positive tumors. (2nd June 2016) - Cheng, Ming; Santich, Brian H.; Xu, Hong; Ahmed, Mahiuddin; Huse, Morgan; Cheung, Nai-Kong V.
ABSTRACT: Engineering potent bispecific antibodies from single-chain variable fragments (scFv) remains difficult due to the inherent instability and insufficient binding of scFv's compared to their parental immunoglobulin format. Previously, we described a scFv-based bispecific antibody (scBA) against disialoganglioside (GD2) based on the anti-GD2 murine 5F11-scFv and the anti-CD3 huOKT3-scFv (5F11-scBA). In this study, we substituted the 5F11-scFv with the higher affinity (13-fold) hu3F8-scFv to form hu3F8-scBA. With this modification, hu3F8-scBA redirected T cells to kill GD2(+) cancer cell lines with up to 5, 000-fold higher potency (femtomolar EC50 ) compared with 5F11-scBA (picomolar EC50 ) in cytotoxicity assays, even against target cells with low GD2 densities. Furthermore, hu3F8-scBA induced stronger T-cell activation than 5F11-scBA, as measured by Ca 2+ flux and cytokine release. Additionally, in vivo, hu3F8-scBA suppressed tumor growth and prolonged mice survival much more effectively than 5F11-scBA, in both neuroblastoma and melanoma xenograft models. We conclude that the functional properties of scBA's can be increased substantially by relatively modest increases in antigen affinity.